Electrochemical biosensor for nitrite based on polyacrylic-graphene composite film with covalently immobilized hemoglobin - Raja Zaidatul Akhmar, Raja Jamaluddin; Heng, Lee Yook; Tan, Ling Ling; K. F., Chong (MDPI, 2018)
A new biosensor for the analysis of nitrite in food was developed based on hemoglobin (Hb) covalently immobilized on the succinimide functionalized poly(n-butyl acrylate)-graphene [poly(nBA)-rGO] composite film deposited on a carbon-paste screen-printed electrode (SPE). The immobilized Hb on the poly(nBA)-rGO conducting matrix exhibited electrocatalytic ability for the reduction of nitrite with significant enhancement in the reduction peak at −0.6 V versus Ag/AgCl reference electrode. Thus, direct determination of nitrite can be achieved by monitoring the cathodic peak current signal of the proposed polyacrylic-graphene hybrid film-based voltammetric nitrite biosensor. The nitrite biosensor exhibited a reproducible dynamic linear response range from 0.05–5 mg L−1 nitrite and a detection limit of 0.03 mg L−1. No significant interference was observed by potential interfering ions such as Ca2+, Na+, K+, NH4+, Mg2+, and NO3− ions. Analysis of nitrite in both raw and processed edible bird’s nest (EBN) samples demonstrated recovery of close to 100%. The covalent immobilization of Hb on poly(nBA)-rGO composite film has improved the performance of the electrochemical nitrite biosensor in terms of broader detection range, lower detection limit, and prolonged biosensor stability.